Consistent effects of independent domestication events on the plant microbiota - Soldan, Riccardo; Fusi, Marco; Cardinale, Massimiliano; Homma, Felix; Santos, Luis Guillermo; Wenzl, Peter; Bach Pages, Marcel; Bitocchi, Elena; Chacon Sanchez, Maria Isabel; Daffonchio, Daniele; Preston, Gail M. (Elsevier, 2024)
The effect of plant domestication on plant-microbe interactions remains difficult to prove. In this study, we provide evidence of a domestication effect on the composition and abundance of the plant microbiota. We focused on the genus Phaseolus, which underwent four independent domestication events within two species (P. vulgaris and P. lunatus), providing multiple replicates of a process spanning thousands of years. We targeted Phaseolus seeds to identify a link between domesticated traits and bacterial community composition as Phaseolus seeds have been subject to large and consistent phenotypic changes during these independent domestication events. The seed bacterial communities of representative plant accessions from subpopulations descended from each domestication event were analyzed under controlled and field conditions. The results showed that independent domestication events led to similar seed bacterial community signatures in independently domesticated plant populations, which could be partially explained by selection for common domesticated plant phenotypes. Our results therefore provide evidence of a consistent effect of plant domestication on seed microbial community composition and abundance and offer avenues for applying knowledge of the impact of plant domestication on the plant microbiota to improve microbial applications in agriculture.